2014
DOI: 10.1111/1462-2920.12407
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of distinct pathways for bacterial degradation of the steroid compound cholate suggests the potential for metabolic interactions by interspecies cross‐feeding

Abstract: SummaryThe distribution and the metabolic pathways of bacteria degrading steroid compounds released by eukaryotic organisms were investigated using the bile salt cholate as model substrate. Cholatedegrading bacteria could be readily isolated from freshwater environments. All isolated strains transiently released steroid degradation intermediates into culture supernatants before their further degradation. Cholate degradation could be initiated via two different reaction sequences. Most strains degraded cholate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(87 citation statements)
references
References 52 publications
2
84
0
Order By: Relevance
“…) according to our previous study (Holert et al . ). HATD has a 3‐keto‐Δ 1,4,6 ‐triene structure of the steroid ring showing that the elimination of water could also occur on steroids without side chain.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…) according to our previous study (Holert et al . ). HATD has a 3‐keto‐Δ 1,4,6 ‐triene structure of the steroid ring showing that the elimination of water could also occur on steroids without side chain.…”
Section: Resultsmentioning
confidence: 96%
“…) and HDOCEA (7α‐hydroxy‐3,12‐dioxo‐4‐cholenoic acid, IV in Fig. ), respectively, according to our previous study (Holert et al ., ). These results suggested that Hsh2 is responsible for the dehydration of these steroid compounds.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…strain Chol2 [50], Zymomonas mobilis ZM4 [30], and Actinoplanes utahensis NRRL 12052 [31] was used for the amplification of hisN homologs from these bacteria.…”
Section: Methodsmentioning
confidence: 99%